Ipsilateral vagotomy to unilaterally ovariectomized pre-pubertal rats modifies compensatory ovarian responses - Chavira Roberto; Bolaños Adán; Ricardo Beatriz; Morales Leticia; Domínguez Roberto (BMC, 2007)
Abstract The present study evaluates the participation of the vagus nerve in pre-pubertal rats with unilateral ovariectomy on puberty onset, and on progesterone, testosterone and estradiol serum levels, and the compensatory responses of the ovary. Unilateral vagotomy did not modify the onset of puberty in unilaterally ovariectomized rats. Ovulation rates of animals with the left vagus nerve sectioned and the left ovary in-situ was lower than in rats with only unilateral ovariectomy. Sectioning the left vagus to 32-day old rats with the left ovary in-situ resulted in lower compensatory ovarian hypertrophy than in rats with right unilateral ovariectomy. Twenty-eight or 32-day old animals with sectioning of the right vagus nerve and the right ovary in situ showed higher compensatory ovulation. Twenty-eight -day old rats with the right ovary in situ had higher progesterone and testosterone levels than animals of the same age with the left ovary in-situ. Compared to animals with the right ovary in situ, animals treated at 32-days of age, sectioning the ipsi-lateral vagus nerve resulted in higher progesterone levels. Higher progesterone levels were observed in 28- and 32 days old rats with the left ovary in situ and left vagus nerve sectioned. Thirty-two day old animals with the right ovary in situ and right vagus nerve sectioned had higher progesterone levels than rats of the same age with the left ovary in situ and left vagus nerve sectioned. Left vagotomy to 28-day old rats with the left ovary in situ resulted in higher testosterone levels, a reverse response to that observed in animals with sectioning of the right vagus and the right ovary in situ. Thirty-two day old rats with the left ovary in situ and left vagus nerve sectioned showed lower testosterone levels than animals without vagotomy and with the left ovary in situ. Twenty-eight -day old animals with the left vagus sectioned and left ovary in situ had lower estradiol serum levels than rats without unilateral vagotomy, a response similar to that observed in 32-day old rats with the right ovary in situ and right vagus nerve sectioned. Present results suggest an asymmetric regulation of steroid hormones secretion by the vagus nerve innervations in animals with unilateral ovariectomy, and those differences in testosterone serum levels observed are associated to the ovary remaining in-situ, vagal innervation and age when the animals were treated.